PENEGAKAN HUKUM DALAM PENANGGULANGAN PROSTITUSI DI KABUPATEN DEMAK - Anastasia Hani Prasetio, Safik Faozi (Fakultas Hukum Universitas Stikubank, 2019)
Prostitution is an act that deviates and violates the rules of social and religious values ​​and norms. Prostitution involving parties such as pimps, commercial sex workers, and service users comes from various circles due to economic factors and lack of mental strength in dealing with global changes in society that changed to the modern era, as well as lifestyle demands where values ​​and norms exist in in society began to be eroded by the changing times that are increasingly developing. The method used in this research is normative juridical, research specifications in concreto, secondary data sources, the data obtained will be analyzed qualitatively. The results showed that law enforcement in the handling of prostitution in Demak Regency was carried out using the model of actual enforcement law. It emerged after the discretion in law enforcement was believed to be due to limitations, both related to infrastructure, quality of human resources, quality of legislation and lack of community participation. Law enforcement officers include the Civil Service Police Unit, Demak District Police, and Social Services. Obstacles that occur in law enforcement in the prevention of prostitution in Demak Regency are due to legal factors including; in the sound of the Regional Regulation numbers are unclear so that it can be bargained in other words not in accordance with these rules, law enforcement factors; law enforcement officials are less assertive, law enforcement officials prioritize the principle of humanity, and the lack of personnel, factors and facilities include; the absence of rehabilitation houses to accommodate community disease perpetrators (CSWs) and lack of funding to crack down on perpetrators to the judicial process, community factors include; the community is less participating in reporting the practice of prostitution around them, and there are backing / thugs or pimps who protect commercial sex workers to provide information early so they can escape, cultural factors include; The inherent community culture has long since begun to be abandoned, and the existence of a modern city culture has entered the Demak District. Keywords: Law Enforcement, Prevention of Prostitution